2020
DOI: 10.1371/journal.pone.0226351
|View full text |Cite
|
Sign up to set email alerts
|

The association between nonalcoholic fatty liver disease and esophageal, stomach, or colorectal cancer: National population-based cohort study

Abstract: We investigated the association between nonalcoholic fatty liver disease (NAFLD) and gastrointestinal tract cancer in the general population. Retrospective data on individuals aged �20 years who received healthcare checkups from January 1, 2009 to December 31, 2009 were analyzed using the National Health Insurance Database in Korea. NAFLD was defined based on the fatty liver index (FLI �60). The primary outcome was newly diagnosed esophageal, stomach, or colorectal cancer using ICD-10 codes during follow-up un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 54 publications
3
42
1
1
Order By: Relevance
“…Lee et al also recently reported an association between NAFLD and esophageal, stomach, or colorectal cancers in Korea [20]. Mortality rates in NAFLD patients with any of these three types of cancer were markedly increased, suggesting a significant association between NAFLD and the risks of esophageal, stomach, or colorectal cancers [20].…”
Section: Introductionmentioning
confidence: 94%
“…Lee et al also recently reported an association between NAFLD and esophageal, stomach, or colorectal cancers in Korea [20]. Mortality rates in NAFLD patients with any of these three types of cancer were markedly increased, suggesting a significant association between NAFLD and the risks of esophageal, stomach, or colorectal cancers [20].…”
Section: Introductionmentioning
confidence: 94%
“…Lee et al also recently reported an association between NAFLD and esophageal, gastric, or colorectal cancers in Korea [20]. Mortality rates in NAFLD patients with any of these three types of cancer were markedly increased, suggesting a significant association between NAFLD and the risks of esophageal, gastric, or colorectal cancers [20].…”
Section: Introductionmentioning
confidence: 95%
“…Lee et al also recently reported an association between NAFLD and esophageal, stomach, or colorectal cancers in Korea [20]. Mortality rates in NAFLD patients with any of these three types of cancer were markedly increased, suggesting a signi cant association between NAFLD and the risks of esophageal, stomach, or colorectal cancers [20].…”
Section: Introductionmentioning
confidence: 95%